A Structural Mechanics Approach for the Vibrational Analysis of Single-Layered Graphene Sheets - Andika Putra; Mikrajuddin Abdullah; Khairurrijal Khairurrijal (Institut Teknologi Bandung, 2009)
A structural mechanics approach has been employed to analyze the vibrational behavior of single-layered graphene sheets. By adopting this approach, natural frequencies and mode shapes are obtained for different chirality and imposed boundary conditions. Numerical results from the implemented modeling are examined to provide predictive equations for fundamental frequencies of cantilevered and bridged graphene sheets. With the proposed equations, the natural frequencies can be predicted and are comparable to those obtained from theoretical consideration and experimental results.